Association between interleukin 37 (rs3811047) polymorphism and multiple autoimmune diseases in a Chinese population: A PRISMA-compliant meta-analysis. Issue 15 (April 2018) - Lin, Xiao-Yan; Guo, Xue-Jun; He, Yu-Zhuo; Hou, Shu-Fang; Zhu, Hong-Bin; Cheng, Ying; Nan, Zhen
Abstract: Objective: Emerging evidence suggests that interleukin 37 (IL-37) plays an important role in the pathogenesis of several autoimmune diseases (ADs), but the correlations are still unclear. We conducted a meta-analysis to explore whether IL-37 gene ( rs3811047 ) polymorphism was associated with susceptibility to multiple ADs in a Chinese population. Methods: Relevant studies were searched in the PubMed, Embase, Chinese National Knowledge Infrastructure, and Chinese Wangfang databases up to August 31, 2017. Odds ratio (OR) and its 95% confidence interval (95% CI) was used to estimate the strength of the association in different genetic models. The results of fixed or random models were adopted according to the heterogeneity. Publication bias and sensitive analysis were also performed to evaluate the reliability of results. Results: A total of 3161 patients and 4078 controls from 6 studies were included in this meta-analysis. Pooling all data together, a significant association between IL-37 gene ( rs3811047 A/G) polymorphism and susceptibility to ADs in the Chinese population was found in all 4 genetic models (allelic model A vs G: OR = 0.73 95% CI = 0.67∼0.79; recessive model AA + AG vs GG: OR = 0.72, 95% CI = 0.65∼0.79; dominant model AA vs AG + GG: OR = 0.59, 95% CI = 0.45∼0.77; homozygous model AA vs GG: OR = 0.55, 95% CI = 0.42∼0.72). No heterogeneity and publication bias was detected in all models. Sensitive analysis indicated that all of the positive results are reliable. Conclusion: The IL- 37 ( rs3811047 ) polymorphism contributes to the development of ADs in a Chinese population.